2016
DOI: 10.3945/ajcn.116.130393
|View full text |Cite
|
Sign up to set email alerts
|

Food quality score and the risk of coronary artery disease: a prospective analysis in 3 cohorts

Abstract: A higher food-based diet quality score was associated with lower risk of CAD and was comparable with established diet scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 46 publications
0
27
0
1
Order By: Relevance
“…Studies have shown that poor dietary quality, characterized by lower intakes of fiber, fruits, vegetables, whole grains, lean protein, and a higher intake of unhealthy fats are associated higher risk for diabetes, 23 cardiovascular diseases, 24 certain types of cancer, 25 decline in physical and cognitive functions, 26,27 fall injuries, 28 hip fractures, 29 and earlier loss of independent living. 30,31 Racial differences in diet quality may contribute to health disparities in older age.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that poor dietary quality, characterized by lower intakes of fiber, fruits, vegetables, whole grains, lean protein, and a higher intake of unhealthy fats are associated higher risk for diabetes, 23 cardiovascular diseases, 24 certain types of cancer, 25 decline in physical and cognitive functions, 26,27 fall injuries, 28 hip fractures, 29 and earlier loss of independent living. 30,31 Racial differences in diet quality may contribute to health disparities in older age.…”
Section: Discussionmentioning
confidence: 99%
“…Food intake over the past year was assessed using the blue 131-item self-reported and semi-quantitative Harvard Food Frequency Questionnaire (FFQ DA 80), which has been extensively validated [ 21 , 22 ]. As described previously, respondents were asked to select one of nine levels for each standardized food item, based on average frequency of consumption in the past year [ 23 ]. The nine options ranged from “never, or less than once per month” to “six or more times per day”.…”
Section: Methodsmentioning
confidence: 99%
“…Unless otherwise indicated, average nutrient intake was calculated by multiplying nutrient values (by mass) from the Harvard University Food Composition Database and the USDA National Nutrient Database for Standard Reference [ 23 , 25 , 26 ]. Results from each source of a particular nutrient were added to represent estimated total intake for specific nutrients.…”
Section: Methodsmentioning
confidence: 99%
“…Poor dietary habits are one of the critical environmental factors for CAD occurrence in general population [ 7 ]. Conversely, healthy dietary patterns—characterized by high intake of low-fat dairy products, whole grains, vegetables, and fruits—are associated with a lower risk of death due to CAD and a lower risk of non-fatal MI incidence within nearly 28 years of observation [ 8 ]. Inadequate nutrition and smoking are highly prevalent among cardiovascular patients [ 9 ] and may cluster with other unfavorable behaviors such as excessive drinking and low activity level [ 10 ], increasing the cumulative effect of multiple risks.…”
Section: Introductionmentioning
confidence: 99%